Nutritional status of children enrolled in municipal early childhood education schools in 2004 and 2018 (Revista Contexto & Saúde, 2025)
This study aims to describe the nutritional status of children enrolled in Municipal Early Childhood Education Schools in the city of Pelotas, RS, in 2004 and 2018. Twenty-four schools were included in 2004, and another 29 were added in 2018. Anthropometric assessment, for both years, was carried out in the schools, following the technical guidelines of the Food and Nutrition Surveillance System. Nutritional status was classified according to body mass index for age according to the growth curves proposed by the World Health Organization. Prevalence was calculated using a significance level of 5%, and the mean BMI of the two studies was compared using the T-test. Statistical analysis was performed using Stata version 15.0. In 2004, about 70% of children were normal; in 2018, this prevalence declined to 54.6%. There was a significant increase in the prevalence of overweight from 2004 (20.9%) to 2018 (26.8%), and higher among girls in both years. The results highlight the nutrition transition in children, highlighting the importance of public policies and actions to promote healthy eating and prevent childhood obesity.
Keywords: Nutritional Status; Preschool; Nutritional Transition; Childhood Obesity